Modern concepts of inflammatory diseases of the pelvic organs - V. V. Skvortsov; E. M. Skvortsova; R. Yu. Bangarov; N. D. Matveev (Лечащий Врач)
Pelvic inflammatory disease is a collective term that includes infectious inflammatory diseases of the upper genital tract of women with the involvement of the uterine (fallopian tubes), ovaries and surrounding tissues. The incidence of inflammatory diseases of the pelvic organs in the world is growing every year, with a particularly clear increase in the incidence in the age groups of 18-24 years (1,4 times) and 25-29 years (1,8 times) over the past decade, which can be a consequence of the early onset of sexual activity. The spectrum of pathogens that cause inflammation of the female genital organs is quite wide and includes both bacteria and sexually transmitted pathogens, which, if there are several ways of infection, increases the risk of pelvic organ disease. The negative effect of the immune response on intracellular metabolism and the functions of the corresponding organs and tissues has been proven. As a result, the clinical effect of treatment decreases and causes the progression and relapses of the disease, and it becomes necessary to search for new ways of prevention and treatment. The importance of inflammatory diseases of the pelvic organs is primarily due to the fact that this group of diseases leads to violations of the reproductive function of women, for example, it can cause the development of infertility in marriage, in particular, tubal and/or peritoneal factors; organic complications such as chronic pelvic pain syndrome. In 15-20% of patients, an acute inflammatory process turns into a chronic one with the development of an adhesive process. Salpingitis and salpingo-oophoritis can lead to the development of adhesive pelvioperitonitis and, as a possible consequence, to the appearance of tubal-peritoneal factor of infertility. For example, women with ascending chlamydial infection with pelvic inflammatory disease may develop Fitz – Hugh – Curtis syndrome (perihepatitis). This article describes the current understanding of PID, as well as the advantage of the drug levofloxacin in the treatment of this group of diseases.